Foreign Exchange Market Organization in Selected Developing and Transition Economies : Evidence from a Survey - Canales Kriljenko, Jorge (IMF Working Papers; Working Paper ;, 2004)
The foreign exchange market microstructures in developing and transition economies are characterized by the results from the IMF's 2001 Survey on Foreign Exchange Market Organization. The survey found that these markets are usually unified onshore spot markets for U.S. dollars, where transactions are concentrated at the bank-customer level. The trading mechanisms are usually dealer or mixed dealer/auction markets; the degree of transparency is often low; settlement systems remain risky; and the scope for price discovery is variable.